Estudio de canción Divino y claro cielode Luis Carrillo y Sotomayor - Cabrera Romero, Lucía (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
Study of the content, structure, style, meter and pragmatics of Luis Carrillo y Soto-mayor composition entitled Divino y claro cielo, paying attention to the edition and transmis-sion of the two printed copies from 1611 and 1613, respectively. I will review the location and context of the composition, giving some details about the biography of the author, who is not affiliated to a single aesthetic current, but com-bines Renaissance themes with an attitude clo-ser to the Baroque in its display of erudition and Mannerism, adapting the topic to the manner, giving priority to the form instead of the style. I will revise his complete work, underlaining some aspects about his historic and aesthetic context within the last third of the sixteenth cen-tury, where there is a great renovation of the highbrow poetry